2020
DOI: 10.3389/fonc.2020.576399
|View full text |Cite
|
Sign up to set email alerts
|

Stroma-Targeting Therapy in Pancreatic Cancer: One Coin With Two Sides?

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is a malignancy with one of the worst prognoses worldwide and has an overall 5-year survival rate of only 9%. Although chemotherapy is the recommended treatment for patients with advanced PDAC, its efficacy is not satisfactory. The dense dysplastic stroma of PDAC is a major obstacle to the delivery of chemotherapy drugs and plays an important role in the progression of PDAC. Therefore, stroma-targeting therapy is considered a potential treatment strategy to improve the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(54 citation statements)
references
References 99 publications
1
53
0
Order By: Relevance
“…Thus, Sonic HedgeHog (SHH), Fibroblast Growth Factor-2 (FGF-2) and Platelet-derived Growth Factor (PDGF) are overexpressed during PDAC and interfering with their signaling corresponds to valuable strategies for PDAC treatment (40,82). However, clinical trials using IPI-926, vismodegib and sonidegib that target the hedgehog pathway have so far been disappointing (123). PDAC cells also overexpress several CXC ligands, which are involved in desmoplastic reaction, immune modulation and tumor angiogenesis (36,124).…”
Section: Matrisome-associated Proteins Secreted Factorsmentioning
confidence: 99%
“…Thus, Sonic HedgeHog (SHH), Fibroblast Growth Factor-2 (FGF-2) and Platelet-derived Growth Factor (PDGF) are overexpressed during PDAC and interfering with their signaling corresponds to valuable strategies for PDAC treatment (40,82). However, clinical trials using IPI-926, vismodegib and sonidegib that target the hedgehog pathway have so far been disappointing (123). PDAC cells also overexpress several CXC ligands, which are involved in desmoplastic reaction, immune modulation and tumor angiogenesis (36,124).…”
Section: Matrisome-associated Proteins Secreted Factorsmentioning
confidence: 99%
“…However, PDAC in Sonic Hedgehog knockout mice show earlier metastasis and thus poorer prognosis [ 16 , 27 ]. Furthermore, several clinical trials targeting stroma in PDAC have shown limited efficacy [ 28 ]. These—in part contradictory—findings indicate the need for further research in this area.…”
Section: Discussionmentioning
confidence: 99%
“…Further prospective studies validating such an approach are required. The impact of tumor cellularity on the response to chemotherapeutic drugs is still subject to research, as promising results of pre-clinical studies investigating stroma-targeted therapy were not fully reproducible in humans so far [ 28 ]. However, in the course of development of personalized medicine techniques, non-invasive prediction of tumor cell content and thus better tumor characterization may contribute to improved individual therapy for PDAC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Pancreatic ductal adenocarcinoma (PDAC) is known for its abundant immunosuppressive stroma, reaching up to 70% of the tumor volume [ 108 ]. Hence, most in vivo studies of adoptive cell therapies reported unsatisfactory outcomes, with the stroma responsible for suppressing ACTs’ anti-PDAC potential.…”
Section: Preclinical Data On Car-nk Cells In Solid Tumorsmentioning
confidence: 99%